2020
DOI: 10.1097/scs.0000000000006473
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Molding of Congenital Ear Deformities: The Impact of Birth-Initiation Delay on Correction Outcome

Abstract: Ear molding can improve the majority congenital ear deformities when employed early after birth. However, the best time to initiate treatment remains debated. In describing one surgeon's experience over the past near decade, this study aims to highlight differences conferred by treatment timing. The authors hypothesize that auricular outcomes are superior when deformities are molded beginning in the first 3 weeks of life. A retrospective review (2010–2018) of 272 cases was performed to compare early initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
14
0
3
Order By: Relevance
“…Congenital ear deformities occur in 5% to 15% of infants [ 14 , 16 ]. Patients with congenital ear deformities tend to suffer psychological distress manifesting as anxiety, low self-esteem, and behavioral problems [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital ear deformities occur in 5% to 15% of infants [ 14 , 16 ]. Patients with congenital ear deformities tend to suffer psychological distress manifesting as anxiety, low self-esteem, and behavioral problems [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… A forest plot of the success rate [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The classic ear-molding method showed substantial efficacy in the treatment of newborn auricular deformities.…”
Section: Figurementioning
confidence: 99%
“…Communicating with empathy, using consistent and simple language, and providing written and visual information are important considerations for healthcare professionals when interacting with families. It is also important to set realistic expectations to help limit discrepancies between expectation and outcome 18…”
Section: Nursing Implicationsmentioning
confidence: 99%
“…Retrospective reviews have shown auricular outcomes to be superior and parents to be satisfied with the outcome 97% of the time, as compared with a satisfaction rate of 85% when treatment was initiated more than 3 weeks after birth. 18 Additional studies have shown that initiating treatment after 6 weeks of life may require prolonged treatment duration due to lower levels of circulating maternal estrogen and resulting firmness of the auricle. 17 Infants with a prominent (or protruding) ear have an increased concha-mastoid angle and/or a flattened antihelical fold (Figure 2).…”
Section: Common Ear Deformationsmentioning
confidence: 99%
See 1 more Smart Citation